Legal protection of medical personnel - Shvechikhina, Annel (Riga Graduate School of Law, 2018)
The research question is what international law instruments provide legal protection of medical personnel during armed conflicts. Medical personnel are a separate group of people that participate in armed conflicts, by providing humanitarian aid to victims. However, there are situations, when the medical personnel themselves need medical aid. In these cases the question arises on what base the medical personnel may obtain the necessary care.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Armed conflicts; Medical personnel